Synthesis of Azoloquinazolines and Substituted Benzothiazepine as Antimicrobial Agents - Kassem, Asmaa F.; Alshehrei, Fatimah; Abbas, Eman M.H.; Farghaly, Thoraya A. (Mini Reviews in Medicinal Chemistry, 2020)
Background & Objective: Quinazolines and their fused systems are noteworthy in pharmaceutical chemistry due to their wide range of biological activities. Methods: A direct and efficient approach for the synthesis of new series of fused quinazolines with triazole, thiazole, benzimidazole and tetrazole has been preceded via the reaction of quinazoline thione derivative with halogenated compounds or cyclocondensation of arylidene of quinazoline derivative with heterocyclic amines. Also, dibenzo[b,e][1,4]thiazepine derivatives was synthesized through the reaction of 2,6-bis-(2-chloro-benzylidene)-cyclohexanone with o-aminothiophenol. Results: The structures of all new synthesized heterocyclic compounds were confirmed and discussed on the bases of spectral data. The utility of the preparation and design of the above mentioned compounds has been shown to be clear in the results of their antimicrobial activity which revealed that some derivatives have potent activity exceeding or similar to the activity of the reference drugs. Conclusion: The insertion of triazole or thiazole moieties to be fused with quinazoline ring helps to enhance its antimicrobial activity.
Keywords: benzothiazepine